The effects of magnesium sulfate therapy after severe diffuse axonal injury - Zhao L; Wang W; Zhong J; Li YY; Cheng YZ; Su Z; Zheng W; Guan XD (Dove Medical Press, 2016)
Ling Zhao,1 Wei Wang,1 Jiwen Zhong,1 YaYun Li,1 YanZi Cheng,1 Zhenjiao Su,1 Wei Zheng,1 Xiang-Dong Guan2 1Department of Critical Care Medicine, Zhuhai People’s Hospital, Zhuhai, Guangdong, 2Department of Critical Care Medicine, The First Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of China Purpose: To evaluate the clinical effects of magnesium sulfate in the treatment of diffuse axonal injury (DAI).Patients and methods: This study was a randomized, double-blind, placebo-controlled trial conducted in the First Affiliated Hospital of Sun Yat-sen University, Guangzhou and Zhuhai People’s Hospital, Zhuhai, two trauma center hospitals. A total of 128 patients suffered from DAI, with initial Glasgow coma scale (GCS) scores of 3–8. They were randomly divided into two groups: magnesium sulfate treatment (MST) group (n=64) and control group (n=64). The MST group received 250 µmol/kg magnesium sulfate intravenously 20 minutes after admission, followed by 750 µmol/kg magnesium sulfate intravenously daily for 5 days. The control group received standard management without MST. GCS scores and serum neuron-specific enolase values were measured and recorded at admission, and on days 3 and 7 after injury. Outcomes were determined by Glasgow outcome scale scores at discharge and at 3 months’ follow-up, respectively.Results: After the 7-day treatment, patients in the MST group, compared with those in the control group, had a lower serum neuron-specific enolase level (25.40±6.66 vs 29.58±7.32, respectively, P=0.001) and higher GCS score (8.23±2.72 vs 7.05±2.64, respectively, P=0.016). Although the length of stay and mortality did not differ between the groups in the intensive care unit, Glasgow outcome scale score was significantly lower in the MST group at discharge (3.30±1.35 vs 3.90±1.10, P=0.004) and 3 months after discharge (2.95±1.48 vs 3.66±1.44, P=0.009).Conclusion: Early treatment with magnesium sulfate resulted in a significant improvement in DAI outcome. Further studies are needed to confirm the clinical significance of treatment of DAI patients with magnesium sulfate. Keywords: diffuse axonal injury, magnesium sulfate, outcome